A simulation-based stereological correction method for assessment of volumetric liberation and surface exposure of ore particles. (January 2022) - Ueda, Takao; Oki, Tatsuya
Graphical abstract: Highlights: A simulation-based stereological correction method was developed. First, a database of liberation distributions is established by simulation. Then, 3D liberation is estimated from 2D liberation, with reference to the database. Volumetric liberation and surface exposure bias can be corrected. Abstract: In assessment of the volumetric liberation and surface exposure of ore particles, two-dimensional (2D) analysis, such as the widely used scanning electron microscope and energy dispersive X-ray (SEM/EDX)-based analysis, results in stereological bias with respect to the three-dimensional (3D) reality. Thus, a simulation-based stereological correction method for accurate assessment of volumetric liberation and surface exposure was developed. The method utilizes a pre-established database of numerically simulated binary particles to estimate 3D composition (or exposure) distributions only from measurable 2D composition (or exposure) distributions. Among the notable features of the method are the relatively small amount of 2D-distribution input data required, and the rapidity of the analysis. Experimental validation, and ex-post analysis of previously published research results, showed high estimation accuracy for various types of particles (including actual ore samples) examined in previous studies. In addition, the method is suitable for post analysis of SEM/EDX-based particle sectional liberation analysis.